Comparing the Efficacy of Probiotic Nutraceuticals and Probiotic Food (Curd) in Combination with Antidepressants for Depression - T. D. Sanmith; Jitendra Chourasiya; Nishant Patel (Archives of Medicine and Health Sciences)
Background and Aim: Depression is a widespread mental health condition with a significant global impact. Recent research has explored the gut–brain axis, emphasizing the role of microbiota in neurotransmitter production. This study aims to explore the effectiveness of two complementary probiotic interventions: probiotic-rich curd and probiotic capsules, used in combination with the antidepressant escitalopram over 4 weeks. The primary objectives include assessing their impact on reducing the severity of depression, comparing their effectiveness, and discussing the clinical implications of findings. Materials and Methods: We conducted a 4-week prospective observational study at the Department of Psychiatry, MGM Medical College, and the associated Mental Hospital in Indore. Ninety individuals aged 18–60, diagnosed with depression (International Classification of Diseases-10) and assessed using the Hamilton Depression Rating Scale, participated. Subjects were divided into three groups: escitalopram 10 mg (n = 30), escitalopram 10 mg + 120 mL curd (n = 30), and escitalopram 10 mg + probiotic capsule (n = 30). Assessments were conducted on days 0, 14, and 28 using the Hamilton Depression Rating Scale. Results: All treatment groups exhibited a significant reduction in mean Hamilton Depression Rating Scale scores over the study duration (P < 0.001). Notably, the probiotic group showed a slightly greater reduction in scores between day 0 and day 28 compared to the curd and escitalopram-only groups. Conclusion: The study demonstrates the potential for slightly better outcomes with probiotic interventions alongside the antidepressant escitalopram over 4 weeks. Beyond symptom relief, this approach may offer lower side effects, potentially enhancing patient adherence. Future research should investigate long-term effects and specific probiotic strains in a larger, diverse population.